2014
DOI: 10.1111/cgf.12417
|View full text |Cite
|
Sign up to set email alerts
|

Importance Sampling Microfacet‐Based BSDFs using the Distribution of Visible Normals

Abstract: Previous: BSDF Importance sampling using the distribution of normals. 64 spp (10.0s)Our: BSDF Importance sampling using the distribution of visible normals. 58 spp (10.4s) Figure 1: A dielectric glass plate (n = 1.5) with anisotropic GGX roughness (αx = 0.05, αy = 0.4) on all faces (with the Smith masking function). For a similar sample budget and the same render time, our method (right) significantly reduces the variance and converges faster than the common technique used in previous work (left). AbstractWe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 12 publications
2
56
0
Order By: Relevance
“…Since our models are a weighted average of multiple lobes, we randomly select one based on the energy and importance sample the visible normals [Heitz and d'Eon 2014] based on the fake incident direction and roughness. However, this strategy is not optimal and creates re ies since the di erent lobes overlap.…”
Section: Forward Modelmentioning
confidence: 99%
“…Since our models are a weighted average of multiple lobes, we randomly select one based on the energy and importance sample the visible normals [Heitz and d'Eon 2014] based on the fake incident direction and roughness. However, this strategy is not optimal and creates re ies since the di erent lobes overlap.…”
Section: Forward Modelmentioning
confidence: 99%
“…An appropriate sampler for microfacet models was introduced by Heitz and d'Eon [Hd14]. Thus, in most cases the variance in the rendered images does not originate in this part of the estimator.…”
Section: Variance With and Without Regularizationmentioning
confidence: 99%
“…In Section 5.4 we present a practical evaluation procedure. Heitz and d'Eon [2014] showed that microfacet BRDF models can be efficiently importance sampled by first sampling a normal from the distribution of visible normals Dω i , and then sampling the micro-BRDF of the material aligned with this normal. The same idea can be applied to importance sampling microflake phase functions: if we importance sample the VNDF Dω i to generate a sample ωm, and then sample an outgoing direction ωo with the micro-phase function p(ωm, ωi → ωo), then ωo follows the PDF given by the dot product of Dω i (ωm) and p(ωm, ωi → ωo).…”
Section: Diffuse Phase Functionmentioning
confidence: 99%